Freezing and melting behaviors of H2O‐NaCl‐CaCl2 solutions in fused silica capillaries and glass‐sandwiched films: implications for fluid inclusion studies. Issue 3 (28th March 2016) - Chu, H.; Chi, G.; Chou, I‐M.
Abstract: Fluid inclusions of the H2 O‐NaCl‐CaCl2 system are notorious for their metastable behavior during cooling and heating processes, which can render microthermometric measurement impossible or difficult and interpretation of the results ambiguous. This study addresses these problems through detailed microscopic examination of synthetic solutions during cooling and warming runs, development of methods to enhance nucleation of hydrates, and comparison of microthermometric results with different degrees of metastability with values predicted for stable conditions. Synthetic H2 O‐NaCl‐CaCl2 solutions with different NaCl/(NaCl + CaCl2 ) ratios were prepared and loaded in fused silica capillaries and glass‐sandwiched films for microthermometric studies; pure solutions were used with the capillaries to simulate fluid inclusions, whereas alumina powder was added in the solutions to facilitate ice and hydrate crystallization in the sandwiched samples. The phase changes observed and the microthermometric data obtained in this study have led to the following conclusions that have important implications for fluid inclusion studies: (i) most H2 O‐NaCl‐CaCl2 inclusions that appear to be completely frozen in the first cooling run to −185°C actually contain large amounts of residual solution, as also reported in some previous studies; (ii) inability of H2 O‐NaCl‐CaCl2 inclusions to freeze completely may be related to their composition (low NaCl/(NaCl + CaCl2 ) ratios) and lack of solid particles; (iii) crystallization of hydrates, which is important for cryogenic Raman spectroscopic studies of fluid inclusion composition, can be greatly enhanced by finding an optimum combination of cooling and warming rates and temperatures; and (iv) even if an inclusion is not completely frozen, the melting temperatures of hydrohalite and ice are still valid for estimating the fluid composition.